2001
DOI: 10.1002/ffj.994
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the essential oil of six Helichrysum species from Madagascar

Abstract: The essential oils of six Helichrysum species from Madagascar were investigated and 46 components were identified by GC, GC-MS and 13 C-NMR spectrometry. The main constituents were 1,8-cineole for H. gymnocephalum (59.7%) and H. bracteiferum (27.3%);ˇ-pinene for H. selaginifolium (38.2%); (E)-caryophyllene for H. cordifolium (55.6%), H. faradifani (34.6%) and H. hypnoides (34.0%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…barrelieri and Helichrysum taenari. 2 8 It was reported that ␤-caryophyllene (24.4%), ␣-pinene (23.2%), ␥-curcumene (5.6%), and rosifoliol (3.1%) were the predominant components of flower essential oil of Helicrysum litoreum. 9 In an earlier study, neryl acetate, nerol, neryl propionate, linalool, eudesm-5-en-11-ol, and ␥-curcumene were identified as the main components.…”
Section: Resultsmentioning
confidence: 99%
“…barrelieri and Helichrysum taenari. 2 8 It was reported that ␤-caryophyllene (24.4%), ␣-pinene (23.2%), ␥-curcumene (5.6%), and rosifoliol (3.1%) were the predominant components of flower essential oil of Helicrysum litoreum. 9 In an earlier study, neryl acetate, nerol, neryl propionate, linalool, eudesm-5-en-11-ol, and ␥-curcumene were identified as the main components.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our on-going work on the characterisation of essential oils from Madagascar, 17 we investigated the bark oil of C. grevei H. Baillon. To our knowledge, the bark oil composition is reported here for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Where Madagascar is concerned, earlier studies have summarised the potentialities in agroforestry of indigenous fruit species but very little work, beyond that of Styger et al (1999) and Carrière et al (2005), has been published on the promotion of medicinal and aromatic plants. And yet, there are numerous fallow species in the eastern forests for which the potentialities are already acknowledged, examples of which include species of Helichrysum genus or Lantana camara (Cavalli et al 2001;Randrianalijaona et al 2005). The model proposed for promoting fallows of P. altissima can thus be extrapolated to other Malagasy fallow plants.…”
Section: Discussionmentioning
confidence: 96%